Review of strength and conditioning for Alpine ski racing - Hydren, J. R.; Volek, J. S.; Maresh, C. M.; Comstock, B. A.; Kraemer, W. J. (Strength and Conditioning Journal, 2013)
The sport of alpine ski racing requires relatively slow eccentric and concentric movements as compared with traditional field sports with course durations from 40 seconds to more than 2 minutes. Controlling the ski snow contact and the ability to limit the dissipation of speed requires dynamic balance and eccentric movement through a wide range of lower limb and hip mobility. Strength and conditioning should focus on hypertrophy, maximal strength, power, balance, dynamic mobility, and anaerobic metabolic support. The purpose of this article is to provide the necessary background for a strength coach to implement as much evidence-based coaching as possible for alpine ski racing.